Fresno County Young Lawyers Association 7th Annual Justice George Hopper Memorial Luncheon - Watkins, Howard::::::::: (1988)
Judge Blaine Pettitt speaking at lectern; seated Fresno County Young Lawyers Association President Brad Hill, Fresno County Bar Association President Herbert Levy, and Deborah Byron